Perkembangan Tektonik Daerah Busur Muka Selat Sunda dan Hubungannya dengan Zona Sesar Sumatera - Lina Handayani; Hery Harjono (Indonesian Institute of Sciences, 2008)
The subduction of the Indian-Australian Plate beneath the Eurasian Plate is oblique ( 45o) along Sumatra. A major zone of dextral strike slip displacement along Sumatra Island, called the Sumatra Fault, partially accommodates the oblique convergence off Sumatra. On the contrary, the subduction is normal along Java; therefore, no major fault zone can be found along the Java Island. The transition zone of the Sunda Strait fore arc, which is located between Java and Sumatra fore arc, is subject to northwest-southeast extension related to the motion of the Sumatra Fault and north-south compression because of subduction. Geophysical studies show that continuous extension dominated the Sunda Strait fore arc region. The results are interpreted as showing ongoing separation of the Sunda Strait fore arc region as the Sumatra fore arc plate has moved northwest, bounded by the Sumatra Fault. Therefore, the Sumatra Fault can also be interpreted to extend across the fore arc to the trench in the form of several graben systems. Key words: Sunda Strait, Sumatra Fault Zone, fore arc tectonic